2022
DOI: 10.3390/healthcare10040705
|View full text |Cite
|
Sign up to set email alerts
|

College Life Adjustment, Life Stress, Career Barriers, and Career Decision-Making Self-Efficacy of College Students Who Have Experienced COVID-19 in South Korea

Abstract: University life is challenging for students, given the college life adjustment, life stress, career barriers, and career decision-making self-efficacy required. COVID-19 has made this even more complex. This study investigated the relationships among these factors in college students who experienced COVID-19. Data were collected using an online cross-sectional structured survey of 1242 university students from December 2020 to January 2021. Data were analyzed via independent-sample t-tests, one-way ANOVAs, Pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The results of our study and other studies in the literature demonstrated that young adults were more worried about their careers, which adversely affected their future career plans. 39 - 41…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study and other studies in the literature demonstrated that young adults were more worried about their careers, which adversely affected their future career plans. 39 - 41…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study and other studies in the literature demonstrated that young adults were more worried about their careers, which adversely affected their future career plans. [39][40][41] Were Healthcare Senior Students' Career Adaptability and Ability to Manage Their Emotions Affected by Some of Their Sociodemographic Characteristics During the COVID-9 Pandemic?…”
Section: Is There Negative Correlation Between Healthcare Senior Stud...mentioning
confidence: 99%
“…Also, individuals with strong goals are those who can react according to their abilities and evaluate themselves, therefore, they are more resilient in the face of setbacks and will develop different plans and strategies to overcome obstacles, thus increasing the likelihood of success (Madrazo & Mariano, 2021). Based on the SCCT, it is believed that CDMSE is an important factor that influences individuals' career goals and career choices (J. H. Park & Kang, 2022;Thompson et al, 2017), and it can effectively predict career-related activity goals and related performance (Xing & Rojewski, 2018). Also, CDMSE has many effects on individuals' career behaviors, and people with high CDMSE have a clearer orientation in their CDM and achievement through their career goals (Monteiro et al, 2021).…”
Section: Research Hypothesismentioning
confidence: 99%
“…The economic downturn caused by the coronavirus disease 2019 (COVID-19) pandemic had substantial repercussions on the job market, with the number of jobs lost reported to be more than four-fold that in the 2009 financial crisis [3]. Consequently, anxiety about the COVID-19 pandemic and employment adversely impacted overall college life [4], and increased perceptions of career barriers hinder students' career preparation behaviors [5].…”
Section: Introductionmentioning
confidence: 99%
“…They include internal psychological and external environmental barriers [9]. Park and Kang [5] reported that career preparation behaviors declined with increased perceptions of barriers. Lee and Jung [10] found a relationship between low level of career preparation and perceived barriers among students.…”
Section: Introductionmentioning
confidence: 99%